2022
DOI: 10.1038/s41420-022-00922-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STAT3Y705 phosphorylation by Stattic suppresses proliferation and induces mitochondrial-dependent apoptosis in pancreatic cancer cells

Abstract: Patients with pancreatic cancer (PC) show dismal prognosis and high mortality. The development of PC is associated with the overactivation of STAT3. Here, we have determined that the non-peptide small molecule Stattic inhibits PC development by targeting STAT3. In vitro, Stattic treatment time- and dose-dependently inhibited proliferation of pancreatic cancer cells (PCCs) by reducing c-Myc expression and enhancing p53 activity. Consequently, p-Rb, cyclin D1, Chk1, and p21 (cell cycle proteins) were downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…However, it should be outlined that a different treatment protocol was used, thus partially explaining the difference observed. In any case, the literature reported controversial results in relation to the role of sorafenib in STAT3 regulation [30,64,65]; therefore, further mechanistic studies both in vitro and in vivo cancer models are expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be outlined that a different treatment protocol was used, thus partially explaining the difference observed. In any case, the literature reported controversial results in relation to the role of sorafenib in STAT3 regulation [30,64,65]; therefore, further mechanistic studies both in vitro and in vivo cancer models are expected.…”
Section: Discussionmentioning
confidence: 99%
“…The marked inhibition of STAT3 exerted by β-caryophyllene oxide could partly explain the higher sorafenib chemosensitization in Bx-PC3 cells with respect to β-caryophyllene. Indeed, several studies have shown that enhancing the STAT3 activation promotes pancreatic cancer malignance and is strongly associated with poor prognosis [30], thus suggesting that targeting STAT3 could potentially be exploited as a promising strategy to fight pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the reduction of endogenous JAK1 or TYK2 by siRNA interference had no effect on the antiviral activity of IMB-0523 against EV71 [Figure 5B], but reducing the endogenous STAT3 by siRNA interference in HCT-8 cells attenuated the antiviral activity of IMB-0523 against EV71 [Figure 5B]. Moreover, stattic, a nonpeptide STAT3 small-molecule inhibitor that effectively inhibits STAT3 activation and nuclear translocation [22,23] also attenuated the antiviral activity of IMB-0523 against EV71 [Figure 5C]. Therefore, IMB-0523 can phosphorylate STAT3 by activating JAK1/TYK2 or directly activate STAT3 to initiate downstream signal transduction to inhibit EV71 replication [Figure 6].…”
Section: Imb-0523 Activates Stat3 Signalingmentioning
confidence: 99%
“…For example, inhibition of mitochondrial respiration could limit the energy supply given to cancer cells . Mitochondria-associated apoptosis , and autophagy can inhibit the growth of cancer cells. Furthermore, interfering and inhibiting mitochondrial metabolism can reduce the support for tumor anabolism, and increasing ROS levels in mitochondria can trigger the mitochondrial oxidative damage to induce the death of cancer cells …”
Section: Introductionmentioning
confidence: 99%